Pristine Lead Oxide Nanocatalyst for Photolytic, Photothermal and Dark Medium Degradation of Murexide - Regmi, Shukra Raj; Khan, Nurul Hoda; Shawd, Narendra Prakash; Shahi, Dikpal Kumar; Khatiwada, Lekha Nath; Ghimire, Rishi Ram; Adhikari, Rameshwar (Amrit Journal, 2025)
Lead oxide nanocatalyst (PbO-NC) is synthesized by the co-precipitation to evaluate its photolytic, photothermal, and dark medium catalytic performance under controlled laboratory conditions. The catalyst is characterized by UV-visible spectroscopy, FTIR, EDX, and XRD techniques; the band gap obtained at 3.70 eV. XRD indicated a tetragonal phase with an average size of 21 nm, and crystallinity of 50.27%. The PbO-NC effectively degraded ammonium purpurate (murexide) under normal solar irradiance (6.91±0.38 kWh/m2/day) with a high-rate constant, i.e., 0.0154 min-1 in light, 0.00412 min-1 in dark, and 0.0158 min-1 in photothermal degradation. The obtained result is higher than other type of oxide-based pure nanocatalytic degradation, and the catalyst is readily recoverable. The catalytic degradation in all circumstances obeyed pseudo-first-order kinetics and efficiencies of 98%, 88%, and 38% in photolytic, photothermal, and dark conditions. Although the synthesis of PbO-NC is tedious and involves toxic precursors, the photosensitive and photothermal properties make it a promising catalyst for degrading heavily toxic dyes.